Environmental Risk Factors for Type 1 Diabetes Mellitus Development - Boljat, Antonela; Gunjača, Ivana; Konstantinović, Ivan; Vidan, Nikolina; Perica, Vesna Boraska; Pehlić, Marina; Škrabić, Veselin; Zemunik, Tatijana (Experimental and Clinical Endocrinology & Diabetes, 2017)
Background Although environmental factors induce development of type 1 diabetes mellitus (T1DM) in genetically susceptible individuals, many of those factors have been uncovered. Therefore, the aim of the present study was to analyze associations of T1DM with a wide range of environmental factors.Material and Methods A case-control study was conducted on 249 diabetic and 255 healthy individuals from the Dalmatian region of South Croatia. Data regarding risk factors during pregnancy and early life period of the child were evaluated.Results History of antihypertensive intake (p=0.04) and frequency of stressful life events during pregnancy (p=0.01) were associated with higher risk of T1DM, while hypertension was associated with lower risk of T1DM (p=0.01). Maternal age<25 years at delivery was associated with a higher risk of T1DM (p=0.01).Diabetic patients had a positive family history of T1DM or T2DM (p=0.002) more frequently than controls, while history of infectious diseases was inversely associated with the risk of T1DM (p=0.03). A higher risk of T1DM was significantly associated with earlier introduction of cow’s milk (p=0.001), higher number of meals consumed per day (p=0.02), higher frequency of carbohydrate (p=0.001) and meat (p=0.01) consumption and stressful life events during childhood (p=0.02) while earlier introduction of fruit was associated with a lower risk of T1DM (p=0.03)Conclusion This case-control study confirmed associations of a large number of environmental factors with development of T1DM with emphasis on the association of mother’s antihypertensive intake during pregnancy, which extends our knowledge about environmental factors related with development of T1DM.
Keywords: type 1 diabetes mellitus; environmental factors; children